Tracheobronchial Foreign Bodies - M. Musharaf Baig, M. Musharaf Baig (Journal of Rawalpindi Medical College, 2007)
foreign bodies, the means by which they gain access and the measures by which accidental aspiration can be prevented. Methods: Bronchoscopy was performed in 39 patients who presented with a suspicion of foreign body aspiration during a three-year period (Jan 2002 – Dec 2004) in the Department of ENT, Holy Family Hospital, Rawalpindi. Results: The common symptoms were sudden onset of dyspnoea and cough. Whistle was commonest object removed (46.15%). Majority of patients were above ten years of age (38.46%). Left main bronchus was the commonest site of involvement. Conclusion: Foreign body aspiration should be suspected when there is sudden onset of respiratory symptoms, even in the absence of a history of aspiration. Emergency bronchoscopy facility should be available in all hospitals. Mass awareness should be created through electronic media and family physicians, to decrease the incidence of such accidents.